Pengaruh Surat Tagihan Pajak dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi - Anne Tonthawi (Jurnal Syntax Transformation, 2021)
The level of compliance of private taxpayers is categorized as low in paying or reporting taxes this causes taxpayers to be subject to administrative sanctions. The purpose of this study is to prove empirically the influence of tax bills and tax credits on compliance of people tax licensees in KPP pratama Cicadas Bandung. This study was conducted at KPP Pratama Bandung Cicadas with as many as 100 samples. Sampling using Random Sampling (Random Sample) with data collection techniques, namely literature research and using primary data (questionnaires). In this study using descriptive and verifiative methods. Data processing is carried out with the SPSS 25 program. The results of this study showed that partially tax bills and tax sanctions significantly affect the compliance of Private Taxpayers in KPP Pratama Cicadas Bandung it is shown by the results of tax collection t_hitung and tax sanctions greater than t_tabel, which means H_0 rejected. Simultaneously tax bills and tax sanctions significantly affect the compliance of Private Taxpayers in KPP Pratama Cicadas Bandung. F test results showed F_hitung was greater F_tabel so H_a accepted. The effect was 37.4% while the other 62.8% was a contribution from other variables that were not studied. Tax bills and tax sanctions partially and simultaneously affect the compliance of private taxpayers.